Problems Affecting a Person's Mood - López-Cortacans, German (2018)
This chapter will focus on problems affecting a person's mood and address some interpretation and intervention models which are relevant to some experiences tested and validated in different contexts, with an emphasis on the role of mental health nurses. Given their prevalence, we will discuss in particular experiences related to depressive symptoms.